2000
DOI: 10.1152/jappl.2000.88.4.1221
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular response to hypoxia after endurance training at altitude and sea level and after detraining

Abstract: The purpose of this study was to elucidate 1) the effects of endurance exercise training during hypoxia or normoxia and of detraining on ventilatory and cardiovascular responses to progressive isocapnic hypoxia and 2) whether the change in the cardiovascular response to hypoxia is correlated to changes in the hypoxic ventilatory response (HVR) after training and detraining. Seven men (altitude group) performed endurance training using a cycle ergometer in a hypobaric chamber of simulated 4,500 m, whereas the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…1), respectively (resting ventilatory chemosensitivity tests were always made before the exercise test). The same hypobaric chamber used in our previous studies (19)(20)(21) was utilized for the exercise test and for intermittent hypoxic exposure. The barometric pressure in the chamber was lowered to 432 Torr over a 30-min period and then held at that level for the next hour.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…1), respectively (resting ventilatory chemosensitivity tests were always made before the exercise test). The same hypobaric chamber used in our previous studies (19)(20)(21) was utilized for the exercise test and for intermittent hypoxic exposure. The barometric pressure in the chamber was lowered to 432 Torr over a 30-min period and then held at that level for the next hour.…”
Section: Subjectsmentioning
confidence: 99%
“…Resting HVR was determined by using a progressive isocapnic hypoxic test (54). A rebreathing system similar to that in our previous studies (19)(20)(21) was used. Tidal volume (VT), inspired minute ventilation (V I), end-tidal CO 2 and O 2 fraction (FET CO 2 and FET O 2 , respectively), and Sa O 2 were measured continuously during rebreathing.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies by Katayama (20)(21)(22) have shown that when the subjects exercise trained for 0.5 h of an approximately 1.5 h of daily IHE, they did not increase their hypoxic ventilatory response, a measure of ventilatory acclimatization. Furthermore, Katayama has shown that exercise training at sea level depresses the hypoxic ventilatory response (20,21).…”
mentioning
confidence: 99%
“…3 Therefore, they show adaptive phenotypic features with respect to physiological parameters such as oxygen saturation, haemoglobin concentration, hypoxic ventilatory rate and blood pressure. [4][5][6][7][8] Studies performed in Sherpas living permanently at high altitude suggest they are genetically better adapted to altitude than populations residing at the same altitude in Andes and highlands of Peru. 9,10 Though samples among highlanders of different part of the world are compared to Himalayan high altitude natives, the comparison among native population at two different altitudes of Himalayan population is performed in this study.…”
Section: Introductionmentioning
confidence: 99%